METAMORPHIC HISTORY OF ECLOGITIC METAGABBRO BLOCKS FROM A TECTONIC MÉLANGE IN THE VOLTRI MASSIF, LIGURIAN ALPS, ITALY - Brouwer, Fraukje M.; Vissers, Reinoud L.M.; Lamb, William M. (Ofioliti, 2002)
Iron/titanium-rich metagabbros, derived from the Beigua serpentinite unit, were collected from a tectonic mélange along the contact between the Beigua serpentinite unit and the underlying Voltri-Rossiglione calcschist unit of the Voltri Group in the Ligurian Alps of northern Italy. Petrographic study and microchemical analysis have been undertaken to unravel the details of their metamorphic history. The metagabbros formed during Jurassic oceanisation in the Piedmont-Ligurian realm, and show local evidence of rodingitisation during ocean-floor metamorphism. Together with the country rock serpentinites, they were subjected to high-pressure metamorphism during Alpine subduction and eventual collision. The high-pressure assemblage in the metagabbro blocks consists of garnet, omphacite, glaucophane, and locally white mica, rutile or titanite. Peak metamorphic conditions, estimated using garnet-omphacite-phengite thermobarometry, were 500 ± 50°C and 17.5 ± 0.5 kbar, i.e. higher peak pressures than previously estimated for these rocks. The rocks cooled continuously during decompression. Exhumation initially proceeded along a low-ÆT/ÆP trajectory, followed by final exhumation along a higher gradient close to that of a continental geotherm. The Voltri Massif had arrived at the Earth’s surface by 34 million years ago, because exhumed rocks of the massif are covered by early Oligocene continental scree breccias and conglomerates. We propose a combination of buoyancy of the serpentinites in the Beigua unit and corner flow in the orogenic wedge on top of the subducting Piedmont- Ligurian oceanic lithosphere as a plausible mechanism to drive exhumation of the high-pressure rocks of the Voltri Massif.